Clinical presentation of tuberculosis: a nine-year single-center experience - Pazarlı, Ahmet Cemal; Ekiz, Timur; Abakay, Mehmet Akif (The European Research Journal, 2018)
Objective. The aim of this study was to determine the clinical presentation of tuberculosis cases from our center for the last nine years.Methods. This study was set as descriptive and retrospective. The data was obtained from the hospital records. Subjects who had been diagnosed as tuberculosis and received treatment in our center between the years 2007 and 2015 were included. The cases were classified as newly diagnosed, relapse, transferred, and returning after default. Results. There were 276 (171 males and 105 females) patients with a mean age of 41.5 ± 19.2 years. Pulmonary involvement is the most common presentation and seen in 155 (56.2%) patients. Lymph node and pleura are the most common extrapulmonary involvements those are seen in 53 (19.2%) and 23 (8.3%) patients, respectively. Number of the cases seems to decreased after 2012.  Most (85.1%) of the patients were newly diagnosed. Among the subjects, 55.2% of them had bacteriologic diagnosis, 35.1% had histopathologic diagnosis. Two subjects died during the treatment period whereas 274 of them completed the treatment program. Conclusions. Our results show that tuberculosis is seen mainly in the adult age group. While pulmonary involvement is the most common presentation, lymph node and pleura involvements are the most common extrapulmonary presentations. Number of the tuberculosis seems to decrease for the recent years. Strict preventive measures and treatment strategies should be administered.